Canine Papillomavirus 2 E6 Does Not Interfere With UVB-Induced Upregulation of p53 and p53-Regulated Genes - Quinlan, Sarah; May, Susan; Weeks, Ryan; Yuan, Hang; Luff, Jennifer (Frontiers in Veterinary Science, 2021)
Cutaneous papillomaviruses are oncogenic viruses that cause severe, persistent infections that can develop into skin cancers within ultraviolet (UV)-exposed skin of immunodeficient individuals, such as those with X-linked severe combined immunodeficiency (XSCID). A canine research model of XSCID exhibits a similar phenotype; these dogs develop severe canine papillomavirus 2 (CPV2) infections that often progress to cancer. Thus, the dog is a natural, spontaneous model to investigate cutaneous papillomavirus infections in immunodeficient patients. The human papillomavirus oncogene E6 contributes to cancer development, in part, by initiating degradation of the tumor suppressor protein p53, or by inhibiting upregulation of p53-dependent genes required within the cell growth arrest, and apoptotic pathways, thereby leading to an accumulation of DNA damage required for oncogenesis. Currently, little is known about CPV2, and how it promotes cancer development. The aim of this study was to determine if CPV2 oncogene E6 similarly affects p53 upon activation by UV radiation, as well as the downstream p53-regulated genes necessary to control growth arrest and apoptosis. We determined that cutaneous CPV2 E6 does not degrade p53, or interfere with the upregulation of p53-regulated genes p21, Bax, Bak, or lncRNA-p21, suggesting that CPV2 may use a p53-independent mechanism to contribute to oncogenesis.